2011
DOI: 10.2131/jts.36.201
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis and CYP4A1 expression in Sprague-Dawley rats exposed to low doses of perfluorooctane sulfonate

Abstract: -In previous studies, perfluorooctane sulfonate (PFOS), an environmental organic compound, was reported to cause hepatotoxicity and hypolipidemia in rodents. However, the low dose toxicity of PFOS and the toxic mechanisms involved remain to be determined. To clarify the low dose toxicity and action mechanism in the target organ toxicity, Sprague-Dawley (SD) rats were orally administered with PFOS at the doses of 0, 1.25, 5, 10 mg/kg/day for 28 days. As a result, no death or abnormal symptoms were observed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 22 publications
(22 reference statements)
4
31
0
Order By: Relevance
“…These results were consistent with similar observations in previous studies evaluating PFOS, perfluoroctanic acid (PFOA), and perfluorinated insecticide N-ethy1-perfluorooctane sulfonamide (N-EtPFOSA) (PedenAdams et al, 2008;Qazi et al, 2009;Kim et al, 2011;Zheng et al, 2011;Elcombe et al, 2012). For example, a recent study by Elcombe et al (2012) evaluated PFOSinduced liver-related effects in male Sprague Dawley rats; following a 7-day dietary exposure to K+PFOS at 20 or 100 ppm, there was a significantly increased liver weight.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results were consistent with similar observations in previous studies evaluating PFOS, perfluoroctanic acid (PFOA), and perfluorinated insecticide N-ethy1-perfluorooctane sulfonamide (N-EtPFOSA) (PedenAdams et al, 2008;Qazi et al, 2009;Kim et al, 2011;Zheng et al, 2011;Elcombe et al, 2012). For example, a recent study by Elcombe et al (2012) evaluated PFOSinduced liver-related effects in male Sprague Dawley rats; following a 7-day dietary exposure to K+PFOS at 20 or 100 ppm, there was a significantly increased liver weight.…”
Section: Discussionsupporting
confidence: 90%
“…For example, a recent study by Elcombe et al (2012) evaluated PFOSinduced liver-related effects in male Sprague Dawley rats; following a 7-day dietary exposure to K+PFOS at 20 or 100 ppm, there was a significantly increased liver weight. Kim et al (2011) also obtained similar results at comparable doses in Sprague-Dawley rats. Those studies also indicated that the increased liver weight might be partially associated with reductions in body weight, since body weight and food intake significantly decreased at higher doses of PFOS.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies showed that the expression of CYPs could be up-regulated by PFOS or PFOA in tested animals (Andersen et al, 2008;Cheng and Klaassen, 2008;Liu et al, 2009a;Kim et al, 2011;NordĂ©n et al, 2012). This induction of CYPs in mice liver by PFOA was demonstrated through activation of PPAR and other transcription factors (Cheng and Klaassen, 2008).…”
Section: The Mechanism Of Enhanced Cytotoxicity Caused By Addition Ofmentioning
confidence: 93%
“…However, other animals such as rats are less sensitive than monkey to PFOS exposure. In fact, the no-observedeadverse-effect level (NOAEL) of PFOS in SpragueeDawley rats orally treated with this xenobiotic, is 1.25 mg/ kg b.w./day in 28-day repeated toxicity studies (Kim et al, 2011). Moreover, the lowest-observed-adverse-effect-level (LOAEL) of PFOS is 1.5 mg/kg b.w./day in adult male rats treated with the chemical in the diet for 4 weeks (Seacat et al, 2003).…”
Section: Introductionmentioning
confidence: 99%